Reconceptualization of Multicultural Islamic Religious Education in Islamic Boarding Schools - Rahmat, Rahmat; Akhmad Sirojuddin (At-Taqaddum, 2025)
Islamic teachings, both in the Quran, Hadith, and the opinions of scholars, require its followers to respect and appreciate differences. In this modern era, respect and appreciation for differences are recognized within the concept of multiculturalism. This multicultural spirit has been practiced in Indonesia, particularly in Islamic boarding schools (pesantren). Long before formal educational institutions existed in Indonesia, pesantren educated students from diverse linguistic, ethnic, and cultural backgrounds through an accessible and integrated system.  The success of Islamic boarding schools in implementing multicultural Islamic education was then adopted by schools, madrasas and universities. One such school that implements this multicultural spirit is a pesantren-based high school under the auspices of the Amanatul Ummah Foundation in Pacet, Mojokerto. Using qualitative research and a case study approach, along with data collection techniques of participant observation, in-depth interviews, and documentation, this study aims to uncover a reconceptualization of multicultural Islamic religious education in pesantren-based schools. The results of this study are: 1) The concept of multicultural Islamic religious education in the Amanatul Ummah Islamic boarding school in Pacet, Mojokerto, with the following characteristics:  with the characteristics of a) Exemplary, b) Cooperation, c) Trust, d) Appreciation, e) Humanity, f) Avoiding bullying, and g) Responsibility and 2) Implications of the concept of multicultural Islamic religious education in the Amanatul Ummah Islamic boarding school-based high school in Pacet, Mojokerto, namely, a) strict strategy in the process and responsible in the results, and b) Superior, Whole, and moral learning model with multicultural insight.